Strategi Manajemen Kurikulum Khas dalam Pengembangan Soft Skills Mutu Lulusan (Studi Kasus : SDIT Ar-Raayah Sukabumi) - Azizah Nur Erlinda; Rizal Firdaus; Husnul Khatimah; Jajat Sudrajat (Halaqa: Journal of Islamic Education, 2026)
The development of graduates’ soft skills is an essential aspect of education, particulary in preparing students to face academic, social, and professional challenges. This study aims to analyze the curriculum management strategies implemented at SDIT Ar Raayah in developing sraduates’ soft skills. This research employed a qualitative approach with a study method. Data were collected through interviews and observation involving the principal, theachers, and students, and were validated through source and method triangulation. The findings indicate that SDIT Ar Raayah implements adistinctive curriculum management strategy that integrates soft skills development into dialy learning and school activities. The curriculum combines Qur’an and Hadith memorization, moral education, Islamic culture (tsaqofah Islamiyah), basic Arabic language, and dialy prayers with various structured activities that foster students’ discipline, responsibility, communication, independence, cooperation, and leadership. The implementation demonstrates that soft skills development is not treated as a separate program but is embedded continously within curriculum planning, implementation, and evaluation. The novelty of this study lies in identifying an integrated curriculum management model that combines Islamic education with systematic soft skills development. These findings imply that curriculum management policies in Islamic shools should provide greater emphasis on integrating character and soft skills development into dialy educational practices rather than focusing primarily on cognitive achievement.